Morphologically Normal-Appearing Adrenal Glands as a Prevalent Source of Aldosterone Production in Primary Aldosteronism. (9th December 2021) - Parksook, Wasita W; Yozamp, Nicholas; Hundemer, Gregory L; Moussa, Marwan; Underhill, Jonathan; Fudim, Tali; Sacks, Barry; Vaidya, Anand
Abstract: Background: Normal-appearing adrenal glands on cross-sectional imaging may still be the source of aldosterone production in primary aldosteronism (PA). Methods: We evaluated the prevalence of aldosterone production among morphologically normal-appearing adrenal glands and the impact of this phenomenon on interpretations of localization studies and treatment decisions. We performed a retrospective cohort study of PA patients with at least 1 normal adrenal gland and reanalyzed contemporary studies to assess interpretations of imaging and adrenal venous sampling (AVS) at the individual patient and adrenal levels. Results: Among 243 patients, 43 (18%) had bilateral normal-appearing adrenals and 200 (82%) had a unilateral normal-appearing adrenal, for a total of 286 normal-appearing adrenal glands. 38% of these normal-appearing adrenal glands were a source of aldosteronism on AVS, resulting in discordance between imaging and AVS findings in 31% of patients. Most patients with lateralizing PA underwent curative unilateral treatment (80%); however, curative treatment was pursued in 92% of patients who had concordant imaging-AVS results but in only 38% who had discordant results ( P < 0.05). In young patients, imaging-AVS discordance was detected in 32% of those under 45 years and 21% of those under 35 years. Among 20 contemporary studies (including 4, 904 patients and 6, 934 normal-appearing adrenal glands), up to 64% of normal-appearing adrenals were a source of aldosteronism resulting in 31% of patients having discordant results. Conclusions: Morphologically normal-appearing adrenal glands are commonly the source of aldosterone production in PA, even among young patients. The lack of awareness of this issue may result in inappropriate treatment recommendations. Graphical Abstract: